Advances of 3D bioprinting technology for periodontal tissue regeneration - Huanhuan Chen; Yu Wang; Yue Lai; Chenda Meng; Xiner Ning; Tianmin Xu; Guangying Song; Yunfan Zhang; Yifan Lin; Bing Han (iScience)
Summary: 3D bioprinting technology for periodontal tissue regeneration is an advanced manufacturing technique that utilizes three-dimensional (3D) printing principles to fabricate intricate, viable structures that are specifically devised to meet with the demand for the periodontal regeneration. Personalized tissue substitutes through 3D bioprinting possesses the capability to promote tissue regeneration in tissue-defective regions. However, the current 3D bioprinting for periodontal tissue engineering still is confronted with many huge challenges that include selecting the optimal rheological properties for precise printing, ensuring the biocompatibility, and facilitating the consistent cell incorporation. In this review, we introduced the pathogenesis of periodontitis and the principle and categories of 3D bioprinting technology. We provided a comprehensive overview of the latest advancements in the application of cutting-edge biofabrication technology of 3D bioprinting for the overall periodontal regeneration, aiming to provide valuable insights for the optimization of 3D bioprinting technology and potential directions for future clinical application.